Capturing digital (in)equity in teaching and learning: a sociocritical approach. Issue 2 (8th March 2019) - Collin, Simon; Brotcorne, Périne
Abstract : Purpose: The purpose of this paper is to present a sociocritical approach and describe how it is relevant to the study of digital equity in education. Design/methodology/approach: The method is based on a synthesis of the literature regarding critical approaches to digital technology in education. Findings: A sociocritical approach is an attempt to formulate a sociological perspective combined with a critical dimension. It provides a relevant theoretical basis for addressing digital (in)equity issues. Originality/value: Little use has been made of critical theories in the study of digital technology in education. That may seem surprising insofar as the study of digital technology in education is related to other fields having a well-established critical tradition. The authors build on their work and tailor it to the case of digital technology in education.